1999
DOI: 10.1038/sj.bjc.6690318
|View full text |Cite
|
Sign up to set email alerts
|

In squamous cell carcinoma of the vulva, overexpression of p53 is a late event and neither p53 nor mdm2 expression is a useful marker to predict lymph node metastases

Abstract: SummaryTo offer more tailored treatment to individual patients with squamous cell carcinoma of the vulva, more accurate prediction of lymph node metastases is required. As p53 and mdm2 are genes known to be involved in the development of other tumours, we studied expression of p53 and mdm2 in carcinogenesis of squamous cell carcinoma of the vulva and their clinical relevance. Archival material of 141 T1 and T2 vulvar tumours were used. Of the 141 primary tumours, the corresponding 39 lymph node metastases (LNM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0
3

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 28 publications
(33 reference statements)
0
14
0
3
Order By: Relevance
“…No relation was found between overexpression of p53 in the primary tumor and lymph node metastases in patients with vulvar carcinoma (70,76,77) .…”
Section: Cell Biologic Parametersmentioning
confidence: 92%
See 1 more Smart Citation
“…No relation was found between overexpression of p53 in the primary tumor and lymph node metastases in patients with vulvar carcinoma (70,76,77) .…”
Section: Cell Biologic Parametersmentioning
confidence: 92%
“…Overexpression of the tumor suppressor gene p53 in squamous cell vulvar carcinomas varies from 39% to 61% in different studies (74)(75)(76)(77)(78)(79)(80) . No relation was found between overexpression of p53 in the primary tumor and lymph node metastases in patients with vulvar carcinoma (70,76,77) .…”
Section: Cell Biologic Parametersmentioning
confidence: 99%
“…We are aware of 11 studies that have examined p53 disruption in HPV-typed vulval neoplasia (Kurvinen et al, 1993;Tervahauta et al, 1993;Lee et al, 1994;Milde-Langosch et al, 1995;Pilotti et al, 1995;Kim et al, 1996;Kagie et al, 1997a, b;Kohlberger et al, 1998;Flowers et al, 1999;Ngan et al, 1999). A further four studies (McConnell et al, 1997;Sliutz et al, 1997;Emanuels et al, 1999;Scheistren et al, 1999) failed to examine HPV status, but two of these included VIN samples (McConnell Emanuels et al, 1999). Combining the data from these studies and our own, it appears that VIN associated with VSCC is significantly more likely to demonstrate aberrant p53 function than lone VIN (Table 5, 25 vs 7%, Po0.0004), suggesting that p53 could be a marker to identify women at risk of progression from VIN to VSCC.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies suggest absent p53 immunoreactivity in lone VIN (Kurvinen et al, 1993;Tervahauta Received 3 October 2002;accepted 9 October 2002accepted 9 October et al, 1993Pilotti et al, 1995;Kohlberger et al, 1998), while others have found 17 -52% p53 immunoreactivity in VIN associated with VSCC (Milde-Langosch et al, 1995;Kagie et al, 1997a ,b;McConnell et al, 1997;Emanuels et al, 1999). It is therefore possible that p53 immunoreactivity could represent a marker for risk of invasion.…”
mentioning
confidence: 99%
“…Many reports show that alterations in p53 may affect the carcinogenesis of the vulva more than that of the cervix, in which HPV infection predominates as a causative agent (3)(4)(5)(6). More recent data suggest that the overexpression of p53 protein is a late event and that the gene is a useful marker to predict lymph node metastasis in squamous cell carcinoma (7)(8)(9)(10).…”
mentioning
confidence: 99%